2019
DOI: 10.1186/s10033-019-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on LCF Behavior of Welded Joint at Different Temperatures for Bainite Steel

Abstract: The current research of low cycle fatigue (LCF) is mainly focused on the components with uniform microstructure. Compared with these typical components, LCF behavior of welded components are more complex due to their great gradient microstructure, especially for different temperature. In this paper, LCF properties were conducted on the welded joint at different temperatures for bainite steel, and the failure mechanism was systematically discussed. Fatigue parameters derived from fitting curves indicated that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, Lan et al 24) reported the optimal range of the size distribution of non-metallic inclusions formed in the weld metal and the essential causes of a deteriorated HAZ toughness. Many authors [25][26][27] reported that the presence of inclusions in welding joints, especially in HAZ, is due to various factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lan et al 24) reported the optimal range of the size distribution of non-metallic inclusions formed in the weld metal and the essential causes of a deteriorated HAZ toughness. Many authors [25][26][27] reported that the presence of inclusions in welding joints, especially in HAZ, is due to various factors.…”
Section: Introductionmentioning
confidence: 99%